Os saberes docentes do orientador de estágio curricular do Curso de Licenciatura em Geografia - Rocha, Luzianny Borges (2018)
This research, whose title is "The Teaching Knowledge of the Curricular Advisor of the Course of Degree in Geography", runs through the link between the concepts: teacher knowledge, instructor teacher and curricular internship in course of licensure. It is the correlation established between these three concepts that guides and clarifies the research and points out its relevance to contribute to the discussions related to the theme, with the strengthening of the area of Geography Teaching and with the qualification of the formative process. Its general objective is to understand the knowledge of the curricular trainer of the UFC Geography Degree Course, correlating with its training and teaching practice in the context of praxis. This research is of a qualitative nature of the ethnomethodological type. The individuals surveyed are three guiding teachers who were followed during the semesters of 2016.1 and 2016.2. The data source is the bibliographic survey and the documentary analysis; and field work is accomplished through the recognition of UFC's Department of Geography, individual and group interviews, and the systematic participant observation of the classroom and photographic records. The research is based on Tardif (2014), Therrien (2014, 2012, 2010, 2006, 1997), Freire (1996, 1987), Imbernón (2009, 2001), Sacristán (1999), Pimenta e Lima Libanea (2011), Veiga (2009), Zabalza (2014), Vázquez (1997), Ribeiro (2010, 1996), Passini (2013), Callai (2003) and Cavalcanti (2002) among other scholars. With the understanding of the teaching knowledge of the three curricular trainees of the Course of Degree in Geography of the UFC, it is concluded that the origin of the knowledge is evidenced in its formation and teaching practice, in the context of praxis, by its personal life history, for their academic background and professional experience.